Engineering circuit analysis - Hayt, William H. Jr.; Kemmerly, Jack E.; Phillips, Jamie D.; Durbin, Steven M. (Singapore : McGraw-Hill, 2019)
The new edition of this text offers expanded coverage of operational amplifiers, new problems using SPICE and new worked-out examples and end-of-chapter problems. It includes added coverage of state space variable analysis.
Chapter 1. Introduction -- Chapter 2. Basic Components and Electric Circuits -- Chapter 3. Voltage and Current Laws -- Chapter 4. Basic Nodal and Mesh Analysis -- Chapter 5. Handy Circuit Analysis Techniques -- Chapter 6. The Operational Amplifier -- Chapter 7. Capacitors and Inductors -- Chapter 8. Basic RL and RC Circuits -- Chapter 9. The RLC Circuit -- Chapter 10. Sinusoidal Steady-State Analysis -- Chapter 11. AC Circuit Power Analysis -- Chapter 12. Polyphase Circuits -- Chapter 13. Magnetically Coupled Circuits -- Chapter 14. Circuit Analysis in the S-Domain -- Chapter 15. Frequency Response -- Chapter 16. Two-Port Networks -- Chapter 17. Fourier Circuit Analysis -- Appendixes.
Includes index.
Keywords: ENGINEERING CIRCUIT ANALYSIS